The contributions of the use of tasks for the teacher training process (Research, Society and Development, 2020)
In this work, we aim to discuss the contributions of the use of tasks to address the important and inherent aspects of the specialized content knowledge, pedagogical content knowledge  and horizon content knowledge with a group of mathematic´s students in the Federal University of Rio de Janeiro. We present a task with two hypothetical solutions of basic education students, and then we propose four questions to the graduating, where they should write them in a paper and after that defend their ideas for the other students in the class. In discussing the solutions and the answers of the students, we teased a series of debates and discussions that made them reflect on the importance of discussing the pedagogical and specific aspects of the teacher's performance in the classroom. The students' performance emphasizes the importance and the need to discuss such issues throughout the undergraduate course, since the first semester of the course.